Is Literacy a Function in Determining the Hemispheric Specialization of Language? - PJ, Kumar; G, Purushothama (Journal of All India Institute of Speech and Hearing)
The authors of this paper have tried to discuss whether literacy has any emphasis in determining cerebral dominance for language. They discuss the possibilities of the same, taking evidence from the research works which have been done earlier.